Red on a rose a novel - Jones, Patricia (Avon Books, 2001)
Lila Giles Calloway's happy life as the wife of a cardiac surgeon in Baltimore is suddenly threatened.
Keywords: Weibliche Schwarze. Amerika; African American families -- Fiction; African American women -- Fiction; Spouses -- Fiction; Baltimore (Md.) -- Fiction; Domestic fiction